Hemipteran Diversity and Genotoxic Effects of Organophosphate In-secticides (Acephate and Profenofos) in Sialkot, Pakistan - Khan, Fatima; Afzal, Rabia (BioScientific Review, 2026)
Background. Agriculture is a cornerstone of Pakistan’s economy and faces significant pest pressure. Hemipteran insects, including aphids, leafhoppers, and true bugs, cause major crop losses and transmit plant pathogens. Methods. This study surveyed the foliage-dwelling Hemiptera in Sialkot district and evaluated the toxicity and genotoxicity of two widely used organophosphate (OP) insecticides, acephate and profenofos. The field survey methods (sweep net and hand collection), insecticide bioassays, micronucleus (MN) assay procedures, and statistical analyses were done. Results. Over a four-month field survey, 1,888 Hemipteran specimens were collected representing 32 species from three suborders. Drosicha corpulenta (a mealybug) and Dysdercus cingulatus (red cotton stainer) were the most abundant, each comprising 31.8% of the total. Acephate and profenofos were tested on D. cingulatus; acephate showed higher acute toxicity (LC50 - 1.2 mL/L) than profenofos (LC50 - 2.0 mL/L). A micronucleus (MN) assay on hemocytes revealed a dose-dependent increase in DNA damage. MN frequencies in D. cingulatus exposed to acephate at LC50 were 4.45%, compared to 4.31% with profenofos, versus 0.3% in controls. These findings indicate that acephate, while being more toxic to target pests, also induced slightly greater genotoxic effects. The results document the diversity of Hemipteran fauna in a key agricultural region and underscore the need for careful insecticide management. Conclusion. This integrated approach—combining biodiversity assessment with toxicological and genotoxic analyses—highlights potential trade-offs between pest control efficacy and sublethal impacts, informing sustainable pest management and conservation strategies.